Comparative study of the seismic performance of Nepalese tiered temples-with and without high plinth consideration. (November 2022) - Kiran Kawan, Chandra; Nath Maskey, Prem; Bahadur Motra, Gokarna
Abstract: The seismic performance of Nepalese multi-tiered temples for two distinct cases –firstly, a tiered temple without a high plinth, and secondly, a tiered temple with a high plinth – are presented in this paper. The seismic assessment of tiered temples undertaken during previous research illustrates that a further evaluation of the role of tiered temples' high plinth may be warranted. As part of this, it is instructive to undertake a comprehensive seismic performance analysis of tiered temples that considers the impact of the presence of high plinths. The field survey was conducted on the three Durbar Squares of the Kathmandu Valley for the selection of the tiered temple with a considerable height of the high plinth. The field investigation was also conducted to establish an in-depth and detailed understanding of the structural components of the selected temples. The selected temples were numerically modeled using the macro-modeling method in SAP2000. The numerical models were updated with the dynamic identification test. The linear time history analysis was done using two earthquake histories -the simulated Lalitpura earthquake and the El Centro earthquake. The seismic response parameters show that a temple with a high plinth is seismically more vulnerable to the impact of earthquakes. The result also indicates the seismic response parameters depend upon the stiffness properties of the high plinth. With the increase in the flexibility of the high plinth, the vulnerability of the tiered temple increases.